2021
DOI: 10.3389/fpsyt.2021.581367
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Anxiety Symptoms and Problematic Smartphone Use Among Chinese University Students: The Mediating/Moderating Role of Self-Efficacy

Abstract: Problematic smartphone use (PSU) is a novel manifestation of addictive behaviors. It is frequently reported to be correlated with anxiety symptoms among University students. However, the underlying mechanism has not yet been thoroughly studied. Whether the association between anxiety symptoms and PSU is mediated or moderated by self-efficacy remains unclarified. A cluster sampling cross-sectional study was thus conducted to explore the potential mediating or moderating effect of self-efficacy in Chinese Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 48 publications
(31 reference statements)
0
23
0
Order By: Relevance
“…Total scores of 50, 60, and 70 were the cut-off scores of mild, moderate, and severe levels of anxiety. The Chinese versions of the PHQ-9 and SAS are both reliable instruments and have been widely used among Chinese adults [ 30 , 33 , 34 , 35 ]. The Cronbach alphas for the PHQ-9 and SAS in this study were 0.91 and 0.87, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Total scores of 50, 60, and 70 were the cut-off scores of mild, moderate, and severe levels of anxiety. The Chinese versions of the PHQ-9 and SAS are both reliable instruments and have been widely used among Chinese adults [ 30 , 33 , 34 , 35 ]. The Cronbach alphas for the PHQ-9 and SAS in this study were 0.91 and 0.87, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Socialization and academic self-efficacy were important factors in smartphone addiction [63]. Studies showed that self-efficacy had an association with the problematic use of mobile devices [64] as it could affect the smartphone addiction [65,66]. In particular, academic self-efficacy was negatively related to smartphone addiction, and it could mitigate the effect of smartphones on academic procrastination [67].…”
Section: Association Between Self-efficacy and Smartphone Addictionmentioning
confidence: 99%
“…The Chinese version of Zung's Self-rating Anxiety Scale (SAS) has been employed to assess participants' anxiety symptoms, which has been widely applied in recent research on university students in the context of COVID-19 [35][36][37]. SAS consists of 20 items, and each item is rated on a scale from 1 to 4.…”
Section: Anxiety Symptomsmentioning
confidence: 99%